Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To determine which term in the sequence [tex]\( T_n = n(n + 2) \)[/tex] is equal to 143, we need to solve the equation [tex]\( n(n + 2) = 143 \)[/tex].
Let's proceed step-by-step:
1. Setting up the equation:
We start with the given sequence formula:
[tex]\[ T_n = n(n + 2) \][/tex]
and set it equal to 143:
[tex]\[ n(n + 2) = 143 \][/tex]
2. Forming a quadratic equation:
Expand the left-hand side:
[tex]\[ n^2 + 2n = 143 \][/tex]
Then, rearrange the equation to standard quadratic form:
[tex]\[ n^2 + 2n - 143 = 0 \][/tex]
3. Solving the quadratic equation:
To solve the quadratic equation [tex]\( n^2 + 2n - 143 = 0 \)[/tex], we can use the quadratic formula, which is given by:
[tex]\[ n = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 1 \)[/tex], [tex]\( b = 2 \)[/tex], and [tex]\( c = -143 \)[/tex]. Plugging in these values, we have:
[tex]\[ n = \frac{-2 \pm \sqrt{2^2 - 4 \cdot 1 \cdot (-143)}}{2 \cdot 1} \][/tex]
Simplifying inside the square root:
[tex]\[ n = \frac{-2 \pm \sqrt{4 + 572}}{2} \][/tex]
[tex]\[ n = \frac{-2 \pm \sqrt{576}}{2} \][/tex]
Since [tex]\( \sqrt{576} = 24 \)[/tex], the equation becomes:
[tex]\[ n = \frac{-2 \pm 24}{2} \][/tex]
4. Finding the roots:
This gives us two potential solutions:
[tex]\[ n = \frac{-2 + 24}{2} = \frac{22}{2} = 11 \][/tex]
and
[tex]\[ n = \frac{-2 - 24}{2} = \frac{-26}{2} = -13 \][/tex]
Therefore, the solutions to the equation are [tex]\( n = 11 \)[/tex] and [tex]\( n = -13 \)[/tex].
Since [tex]\( n = -13 \)[/tex] is a negative term and may not typically be considered in the context of sequence terms, we focus on the positive integer solution.
Conclusion:
The term in the sequence [tex]\( T_n = n(n + 2) \)[/tex] that equals 143 is the 11th term.
Let's proceed step-by-step:
1. Setting up the equation:
We start with the given sequence formula:
[tex]\[ T_n = n(n + 2) \][/tex]
and set it equal to 143:
[tex]\[ n(n + 2) = 143 \][/tex]
2. Forming a quadratic equation:
Expand the left-hand side:
[tex]\[ n^2 + 2n = 143 \][/tex]
Then, rearrange the equation to standard quadratic form:
[tex]\[ n^2 + 2n - 143 = 0 \][/tex]
3. Solving the quadratic equation:
To solve the quadratic equation [tex]\( n^2 + 2n - 143 = 0 \)[/tex], we can use the quadratic formula, which is given by:
[tex]\[ n = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 1 \)[/tex], [tex]\( b = 2 \)[/tex], and [tex]\( c = -143 \)[/tex]. Plugging in these values, we have:
[tex]\[ n = \frac{-2 \pm \sqrt{2^2 - 4 \cdot 1 \cdot (-143)}}{2 \cdot 1} \][/tex]
Simplifying inside the square root:
[tex]\[ n = \frac{-2 \pm \sqrt{4 + 572}}{2} \][/tex]
[tex]\[ n = \frac{-2 \pm \sqrt{576}}{2} \][/tex]
Since [tex]\( \sqrt{576} = 24 \)[/tex], the equation becomes:
[tex]\[ n = \frac{-2 \pm 24}{2} \][/tex]
4. Finding the roots:
This gives us two potential solutions:
[tex]\[ n = \frac{-2 + 24}{2} = \frac{22}{2} = 11 \][/tex]
and
[tex]\[ n = \frac{-2 - 24}{2} = \frac{-26}{2} = -13 \][/tex]
Therefore, the solutions to the equation are [tex]\( n = 11 \)[/tex] and [tex]\( n = -13 \)[/tex].
Since [tex]\( n = -13 \)[/tex] is a negative term and may not typically be considered in the context of sequence terms, we focus on the positive integer solution.
Conclusion:
The term in the sequence [tex]\( T_n = n(n + 2) \)[/tex] that equals 143 is the 11th term.
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.